Quantitative Imaging In Vivo of Functioning Lymphatic Vessels Around Human Melanoma and Benign Nevi. (August 2015) - Akhras, Victoria; Ramakrishnan, Rathi; Stanton, Anthony W.B.; Levick, John R.; Cook, Martin G.; Chong, Heung; Mortimer, Peter S.
Abstract Objectives The density of functioning human lymphatics in vivo and of immunohistochemically defined lymphatics was quantified around melanomas, benign nevi, and matched normal skin, to assess the current lymphangiogenesis paradigm. We investigated whether histological and functioning density increased around melanomas compared with benign nevi or matched skin; whether functioning and histological density increased similarly; and whether larger increases occurred around metastatic melanomas. Methods Functioning density was quantified in vivo as the total amount of human dermal microlymphatics taking up fluorescent marker injected at the lesion margin. After tissue excision, perilesion histological density was quantified using podoplanin marker D2‐40. Results Histological density was raised similarly around metastasising and non‐metastasising melanomas compared with normal skin (+71%, p < 0.0001, n = 32); but was also raised significantly around benign nevi (+17%, p = 0.03, n = 20). In contrast, functioning lymphatic density was substantially reduced around the margins of melanomas (both metastasising and non‐metastasising) compared with benign nevi (by 65%, p = 0.02) or normal skin (by 53%, p = 0.0014). Conclusions Raised perilesion histological lymphatic density is not unique to melanoma but occurs also around benign nevi. The findings indicated that the number of functioning lateral lymphatics around human melanomas in vivo but not benign nevi is reduced, despite histologically increased numbers of lymphatics.